Zero-silicon artificial board and manufacturing process thereof
Through the combination of modified powder and modified unsaturated polyester resin, the existing problem of high production costs of silicon -free slate materials and poor stone texture have been solved, and boards with lower cost and better performance have been achieved.
Patent Information
- Application Number
- CN202411456642.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-21
AI Technical Summary
The existing silicon-free artificial stone slabs use aluminum powder as filler, resulting in high production costs and poor stone texture.
Modified powder and modified unsaturated polyester resin are used to cover nanal calcium carbonate through lipidic acid and formed a high polymer layer to improve the gloss, light transmission and impact resistance of the plate.
Reduced the production cost of the board, improved the texture of the stone, and improved the luster, light transmission and impact resistance of the plate.
Smart Images

Figure BDA0005090652020000071 
Figure BDA0005090652020000081
Abstract
Description
Technical Field
[0001] The invention relates to the field of artificial boards, in particular to a zero-silicon artificial board and also to a manufacturing process of the board. Background Art
[0002] Traditional artificial stone is generally made of quartz stone, resin, coupling agent, curing agent, etc. Silicon-free artificial stone is a polymer synthetic material. Unlike traditional artificial stone, it does not contain silicon components. It has unique advantages in some specific application scenarios and is widely used in kitchen countertops, bathroom decorations, interior walls and commercial spaces.
[0003] Reference is now made to the invention patent with application number 202410339748.8, a high-hardness silicon-free artificial stone board and its preparation method, which discloses the following content: The silicon-free artificial stone board, calculated by weight, includes the following components: 25-35 parts of unsaturated polyester resin, 55-75 parts of modified aluminum powder, 2-6 parts of carbon fiber, 1.5-3.5 parts of curing agent and 0.3-3 parts of pigment. However, the silicon-free artificial stone of the aforementioned technology is composed of aluminum powder, resin and other additives, and aluminum powder is used as a filler to replace traditional quartz stone. However, the source of aluminum powder is small and the cost is high, which makes the production cost of the board high. In addition, the board made with aluminum powder as filler also has the problem of poor stone texture. Summary of the invention
[0004] In view of the above-mentioned shortcomings of the prior art, the object of the present invention is to provide a zero-silicon artificial board and a production process thereof to produce a non-crystalline silicon board with good gloss and light transmittance and excellent impact resistance.
[0005] A zero-silicon artificial board comprises the following components: modified powder, modified unsaturated polyester resin, toughening agent, white paste, curing agent and coupling agent are mixed to obtain the zero-silicon artificial board; wherein the modified powder is obtained by surface chemical coating modification of nano calcium carbonate, and the surface of the modified powder has a polymer layer; and the unsaturated polyester resin is modified by using styrene to obtain the modified unsaturated polyester resin.
[0006] In one embodiment, a method for obtaining the modified powder by surface chemical coating of nano calcium carbonate is specifically performed as follows: stearic acid is added to a nano calcium carbonate-n-butanol suspension to obtain a modified nano calcium carbonate powder, and then a vinyl compound is added for reaction to obtain the modified powder. In the present invention, stearic acid is coated on the surface of nano calcium carbonate to make it organic, thereby improving the acid resistance of calcium carbonate. Olefin monomers are used to perform in-situ polymerization on the surface of nano calcium carbonate under the action of an inorganic initiator, and a polymer layer with a core-shell structure is formed on the surface of calcium carbonate particles. The polymer is directionally adsorbed to the surface of calcium carbonate to form an effective adsorption layer, thereby reducing the agglomeration of calcium carbonate particles, improving dispersibility, and improving the dispersion performance during use, so as to achieve the purpose of improving light transmittance, so that the plate made thereof has good gloss and light transmittance.
[0007] In one embodiment, the method for modifying an unsaturated polyester resin using styrene to obtain the modified unsaturated polyester resin is specifically performed as follows: styrene and the unsaturated polyester resin are blended at 50-60°C.
[0008] Furthermore, the blending modification is carried out in a closed reactor, and the amount of styrene added accounts for 2% to 5% of the polyester resin, and the closed reactor is used to prevent the volatilization of styrene. The present invention utilizes styrene to react with the unsaturated polyester resin to form a dense polymer structure, thereby improving the impact resistance and tensile strength of the unsaturated polyester resin.
[0009] In one of the embodiments, the weight ratio of the modified powder, modified unsaturated polyester resin and toughening agent is 16-30:6-10:1, and the white paste, curing agent and coupling agent account for 3.5% to 5.8% of the total amount.
[0010] Furthermore, the weight proportion of the zero-silicon artificial board is as follows: 60-80 parts of modified powder, 20-30 parts of modified unsaturated polyester resin, 2-5 parts of toughening agent, 0.2-0.8 parts of white paste, 2-4 parts of curing agent, and 1-2 parts of coupling agent. The toughening agent is any one of ethylene-propylene rubber, polybutadiene rubber and butyl rubber. In the present invention, the toughening agent is added to disperse stress, absorb impact and improve fracture toughness, thereby effectively improving the toughness of the prepared board.
[0011] Furthermore, the zero-silicon artificial board is composed of the following parts by weight: 75 parts of modified powder, 28 parts of modified unsaturated polyester resin, 4 parts of toughening agent, 0.6 parts of white pulp, 3.4 parts of curing agent, and 2 parts of coupling agent.
[0012] Furthermore, the curing agent is methyl ethyl ketone peroxide, dibenzoyl peroxide, tert-butyl perbenzoate or fatty polyamine. The coupling agent is any one of aniline methyl triethoxysilane, vinyl triethoxysilane, vinyl trimethoxysilane and γ-chloropropyl triethoxysilane.
[0013] A process for producing an artificial board, which is used to produce the zero-silicon artificial board, comprises the following steps:
[0014] S1: dispersing nano calcium carbonate in n-butanol, and dehydrating by azeotropic distillation to obtain a nano calcium carbonate-n-butanol suspension;
[0015] S2 adding stearic acid to the nano calcium carbonate-n-butanol suspension to obtain modified nano calcium carbonate powder;
[0016] S3 adds a vinyl compound, which reacts with the modified nano calcium carbonate powder under the action of potassium persulfate to obtain a modified powder for later use;
[0017] S4: using styrene to modify the unsaturated polyester resin to obtain the modified unsaturated polyester resin;
[0018] S5: mixing and stirring the modified powder, the modified unsaturated polyester resin, the white paste, the toughening agent, the curing agent and the coupling agent to obtain a mixture;
[0019] S6: unloading the mixed material into a preset mold frame, flattening the material, covering it with paper, pressing it into shape, and then curing it to obtain a sheet material;
[0020] S7 grinds the sheet material to obtain an artificial sheet.
[0021] In one embodiment, the curing process is carried out in a curing oven, the curing temperature is 75-85° C., and the curing time is 60-90 min.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The invention adopts stearic acid to coat the surface of nano calcium carbonate to make it organic so as to improve the acid resistance of calcium carbonate, and further utilizes olefin monomers to carry out in-situ polymerization on the surface of nano calcium carbonate under the action of inorganic initiators to form a polymer layer with a core-shell structure on the surface of calcium carbonate particles to obtain modified powder, and manufactures artificial plates with good gloss and light transmittance. Compared with aluminum powder, the modified powder has better stone texture and wider source, thereby reducing the production cost of the plates.
[0024] The present invention introduces an aromatic ring structure into an unsaturated polyester resin to improve the strength of the unsaturated polyester resin, so that the tensile strength and bending strength of the modified unsaturated polyester resin are improved, thereby producing a plate with excellent impact resistance. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. Additional aspects and advantages of the present invention will be given in part in the following description, and will become apparent from the following description, or will be understood through the practice of the present invention. It should be understood that the following description is only used to explain the present invention and is not intended to limit the present invention.
[0026] As used herein, the terms "comprises," "including," "contains," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0027] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range limited by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including a range of "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When a numerical range is described in this article, unless otherwise specified, the range is intended to include its end values and all integers and fractions within the range.
[0028] The specific embodiments of the present invention are described in detail below.
[0029] Example 1
[0030] This embodiment provides a zero-silicon artificial board, which has the following components: modified powder, modified unsaturated polyester resin, ethylene-propylene rubber, white pulp, methyl ethyl ketone peroxide and aniline methyl triethoxysilane are mixed to obtain the zero-silicon artificial board. The modified powder is obtained by surface chemical coating modification of nano calcium carbonate, and the surface of the modified powder has a polymer layer. The unsaturated polyester resin is modified by using styrene to obtain the modified unsaturated polyester resin.
[0031] The zero-silicon artificial board is composed of the following parts by weight: 60 parts of modified powder, 20 parts of modified unsaturated polyester resin, 2 parts of ethylene-propylene rubber, 0.2 parts of white pulp, 2 parts of methyl ethyl ketone peroxide, and 1 part of aniline methyl triethoxysilane. The zero-silicon artificial board of this embodiment has the following production process:
[0032] S1: dispersing nano calcium carbonate in n-butanol, and dehydrating by azeotropic distillation to obtain a nano calcium carbonate-n-butanol suspension.
[0033] S2: adding stearic acid to the nano calcium carbonate-n-butanol suspension to obtain modified nano calcium carbonate powder.
[0034] S3 adds a vinyl compound, which reacts with the modified nano calcium carbonate powder under the action of potassium persulfate to obtain a modified powder for later use.
[0035] S4: blending styrene and unsaturated polyester resin in a closed reactor at 50° C. to obtain modified unsaturated polyester resin, wherein the amount of styrene added accounts for 2% of the polyester resin.
[0036] S5: mixing and stirring the modified powder, modified unsaturated polyester resin, white paste, ethylene-propylene rubber, methyl ethyl ketone peroxide and aniline methyl triethoxy silane to obtain a mixture.
[0037] S6 unloads the mixed material into a preset mold frame, flattens the material, covers it with paper, presses it into shape, and then performs a curing treatment to obtain a sheet material. The curing treatment is performed in a curing furnace at a curing temperature of 75°C and a curing time of 90 minutes.
[0038] S7 grinds the sheet material to obtain an artificial sheet.
[0039] Example 2
[0040] The present embodiment provides a zero-silicon artificial board, which has the following components: modified powder, modified unsaturated polyester resin, polybutadiene rubber, white pulp, dibenzoyl peroxide and vinyl triethoxysilane are mixed to obtain the zero-silicon artificial board. The modified powder is obtained by surface chemical coating modification of nano calcium carbonate, and the surface of the modified powder has a polymer layer. The unsaturated polyester resin is modified by using styrene to obtain the modified unsaturated polyester resin.
[0041] The zero-silicon artificial board is composed of the following parts by weight: 65 parts of modified powder, 24 parts of modified unsaturated polyester resin, 3 parts of polybutadiene rubber, 0.4 parts of white pulp, 2.6 parts of dibenzoyl peroxide, and 1 part of vinyl triethoxysilane. The zero-silicon artificial board of this embodiment has the following production process:
[0042] S1: dispersing nano calcium carbonate in n-butanol, and dehydrating by azeotropic distillation to obtain a nano calcium carbonate-n-butanol suspension.
[0043] S2: adding stearic acid to the nano calcium carbonate-n-butanol suspension to obtain modified nano calcium carbonate powder.
[0044] S3 adds a vinyl compound, which reacts with the modified nano calcium carbonate powder under the action of potassium persulfate to obtain a modified powder for later use.
[0045] S4: blending styrene and unsaturated polyester resin in a closed reactor at 54° C. to obtain modified unsaturated polyester resin, wherein the amount of styrene added accounts for 3% of the polyester resin.
[0046] S5: mixing and stirring the modified powder, modified unsaturated polyester resin, white paste, polybutadiene rubber, dibenzoyl peroxide and vinyl triethoxysilane to obtain a mixture.
[0047] S6 unloads the mixed material into a preset mold frame, flattens the material, covers it with paper, presses it into shape, and then performs a curing treatment to obtain a sheet material. The curing treatment is carried out in a curing furnace at a curing temperature of 77° C. and a curing time of 80 minutes.
[0048] S7 grinds the sheet material to obtain an artificial sheet.
[0049] Example 3
[0050] The present embodiment provides a zero-silicon artificial board, which has the following components: modified powder, modified unsaturated polyester resin, butyl rubber, white pulp, fatty polyamine and vinyl trimethoxy silane are mixed to obtain the zero-silicon artificial board. The modified powder is obtained by surface chemical coating modification of nano calcium carbonate, and the surface of the modified powder has a polymer layer. The unsaturated polyester resin is modified by using styrene to obtain the modified unsaturated polyester resin.
[0051] The zero-silicon artificial board is composed of the following parts by weight: 75 parts of modified powder, 28 parts of modified unsaturated polyester resin, 4 parts of butyl rubber, 0.6 parts of white pulp, 3.4 parts of fatty polyamine, and 2 parts of vinyl trimethoxy silane. The zero-silicon artificial board of this embodiment has the following production process:
[0052] S1: dispersing nano calcium carbonate in n-butanol, and dehydrating by azeotropic distillation to obtain a nano calcium carbonate-n-butanol suspension.
[0053] S2: adding stearic acid to the nano calcium carbonate-n-butanol suspension to obtain modified nano calcium carbonate powder.
[0054] S3 adds a vinyl compound, which reacts with the modified nano calcium carbonate powder under the action of potassium persulfate to obtain a modified powder for later use.
[0055] S4: blending styrene and unsaturated polyester resin in a closed reactor at 58° C. to obtain modified unsaturated polyester resin, wherein the amount of styrene added accounts for 4% of the polyester resin.
[0056] S5: mixing and stirring the modified powder, modified unsaturated polyester resin, white paste, butyl rubber, fatty polyamine and vinyl trimethoxy silane to obtain a mixture.
[0057] S6 unloads the mixed material into a preset mold frame, flattens the material, covers it with paper, presses it into shape, and then performs a curing treatment to obtain a sheet material. The curing treatment is carried out in a curing furnace at a curing temperature of 82° C. and a curing time of 70 minutes.
[0058] S7 grinds the sheet material to obtain an artificial sheet.
[0059] Example 4
[0060] The present embodiment provides a zero-silicon artificial board, which has the following components: modified powder, modified unsaturated polyester resin, butyl rubber, white pulp, tert-butyl peroxybenzoate and γ-chloropropyltriethoxysilane are mixed to obtain the zero-silicon artificial board. The modified powder is obtained by surface chemical coating modification of nano calcium carbonate, and the surface of the modified powder has a polymer layer. The unsaturated polyester resin is modified by using styrene to obtain the modified unsaturated polyester resin.
[0061] The zero-silicon artificial board is composed of the following by weight: 80 parts of modified powder, 30 parts of modified unsaturated polyester resin, 5 parts of butyl rubber, 0.8 parts of white pulp, 4 parts of tert-butyl perbenzoate, and 2 parts of γ-chloropropyltriethoxysilane. The zero-silicon artificial board of this embodiment has the following production process:
[0062] S1: dispersing nano calcium carbonate in n-butanol, and dehydrating by azeotropic distillation to obtain a nano calcium carbonate-n-butanol suspension.
[0063] S2: adding stearic acid to the nano calcium carbonate-n-butanol suspension to obtain modified nano calcium carbonate powder.
[0064] S3 adds a vinyl compound, which reacts with the modified nano calcium carbonate powder under the action of potassium persulfate to obtain a modified powder for later use.
[0065] S4: blending styrene and unsaturated polyester resin in a closed reactor at 60° C. to obtain modified unsaturated polyester resin, wherein the amount of styrene added accounts for 5% of the polyester resin.
[0066] S5: mixing and stirring the modified powder, modified unsaturated polyester resin, white paste, butyl rubber, tert-butyl perbenzoate and γ-chloropropyltriethoxysilane to obtain a mixture.
[0067] S6 unloads the mixed material into a preset mold frame, flattens the material, covers it with paper, presses it into shape, and then performs a curing treatment to obtain a sheet material. The curing treatment is carried out in a curing furnace at a curing temperature of 85°C and a curing time of 60 minutes.
[0068] S7 grinds the sheet material to obtain an artificial sheet.
[0069] Comparative Example 1
[0070] The only difference between Comparative Example 1 and Example 3 is that ordinary calcium powder is used instead of modified powder.
[0071] Comparative Example 2
[0072] The difference between Comparative Example 2 and Example 3 is that unsaturated polyester resin is used instead of modified unsaturated polyester resin.
[0073] Comparative Example 3
[0074] The only difference between Comparative Example 3 and Example 3 is that no toughening agent is added.
[0075] The artificial boards of Examples 1 to 4 and Comparative Examples 1 to 3 were subjected to corrosion tests and impact strength tests, respectively. The operation process of the corrosion test is as follows: hydrochloric acid is dripped onto the board to observe whether bubbles are generated, and after 24 hours, whether there are corrosion marks on the surface of the board. The specific test process of the impact strength test is not described in detail, and the test results are shown in Table 1.
[0076] Table 1:
[0077]
[0078]
[0079] From the comparative analysis of Table 1, it can be seen that the zero-silicon artificial board of the present invention has significantly improved acid resistance compared with the untreated calcium powder, so that the prepared board has good corrosion resistance. In addition, the impact resistance of the prepared board is improved by combining the modified unsaturated polyester resin with a toughening agent, so that it can withstand higher impact and stress and has good durability.
[0080] The above embodiments are merely preferred implementations of the present invention. Any simple modification, amendment and substitution of the above embodiments based on the technical essence of the present invention shall fall within the scope of the technical solution of the present invention.
Claims
1. A zero-silicon artificial board, characterized in that: The zero-silicon artificial board has the following components: modified powder, modified unsaturated polyester resin, toughening agent, white paste, curing agent and coupling agent are mixed to obtain the zero-silicon artificial board; The modified powder is obtained by performing surface chemical coating modification on the nano calcium carbonate, and the surface of the modified powder has a polymer layer; the unsaturated polyester resin is modified by using styrene to obtain the modified unsaturated polyester resin.
2. The zero-silicon artificial board according to claim 1, characterized in that: The method for obtaining the modified powder by surface chemical coating modification of nano calcium carbonate is specifically performed as follows: adding stearic acid to a nano calcium carbonate-n-butanol suspension to obtain modified nano calcium carbonate powder, and then adding a vinyl compound for reaction to obtain the modified powder.
3. The zero-silicon artificial board according to claim 1, characterized in that: The method for modifying unsaturated polyester resin by using styrene to obtain the modified unsaturated polyester resin is specifically performed as follows: styrene and unsaturated polyester resin are blended at 50-60°C.
4. The zero-silicon artificial board according to claim 3, characterized in that: The blending modification is carried out in a closed reaction kettle, and the added amount of styrene accounts for 2% to 5% of the polyester resin.
5. The zero-silicon artificial board according to claim 1, characterized in that: The weight ratio of the modified powder, modified unsaturated polyester resin and toughening agent is 16-30:6-10:1, and the white paste, curing agent and coupling agent account for 3.5%-5.8% of the total amount.
6. The zero-silicon artificial board according to claim 5, characterized in that: The zero-silicon artificial board is composed of the following parts by weight: 60-80 parts of modified powder, 20-30 parts of modified unsaturated polyester resin, 2-5 parts of toughening agent, 0.2-0.8 parts of white pulp, 2-4 parts of curing agent, and 1-2 parts of coupling agent; The toughening agent is any one of ethylene-propylene rubber, polybutadiene rubber and butyl rubber.
7. The zero-silicon artificial board according to claim 6, characterized in that: The zero-silicon artificial board is composed of the following parts by weight: 75 parts of modified powder, 28 parts of modified unsaturated polyester resin, 4 parts of toughening agent, 0.6 parts of white pulp, 3.4 parts of curing agent, and 2 parts of coupling agent.
8. The zero-silicon artificial board according to claim 7, characterized in that: The curing agent is methyl ethyl ketone peroxide, dibenzoyl peroxide, tert-butyl perbenzoate or fatty polyamine; The coupling agent is any one of aniline methyl triethoxysilane, vinyl triethoxysilane, vinyl trimethoxysilane and γ-chloropropyl triethoxysilane.
9. A process for producing an artificial board, which is used to produce the zero-silicon artificial board as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: S1: dispersing nano calcium carbonate in n-butanol, and dehydrating by azeotropic distillation to obtain a nano calcium carbonate-n-butanol suspension; S2 adding stearic acid to the nano calcium carbonate-n-butanol suspension to obtain modified nano calcium carbonate powder; S3 adds a vinyl compound, which reacts with the modified nano calcium carbonate powder under the action of potassium persulfate to obtain a modified powder for later use; S4: using styrene to modify the unsaturated polyester resin to obtain the modified unsaturated polyester resin; S5: mixing and stirring the modified powder, the modified unsaturated polyester resin, the white paste, the toughening agent, the curing agent and the coupling agent to obtain a mixture; S6: unloading the mixed material into a preset mold frame, flattening the material, covering it with paper, pressing it into shape, and then curing it to obtain a sheet material; S7 grinds the sheet material to obtain an artificial sheet.
10. The process for producing the artificial board according to claim 9, characterized in that: The curing treatment is carried out in a curing oven, the curing temperature is 75-85° C., and the curing time is 60-90 minutes.
Citation Information
Patent Citations
High-hardness silicon-free artificial stone plate and preparation method thereof
CN118255545A
Cited By
Zero-silicon plate and preparation process thereof
CN121627338A
Composite carbon black material for artificial stone as well as preparation method and application of composite carbon black material
CN121990784A